Allocating Selling Effort Via Dynamic Programming - Beswick, Charles A. (Management Science, 1977)
This article presents a model for allocating selling effort and setting sales force size which explicitly considers interactions with territorial design, forecasting, and performance evaluation. An extremely fast, dynamic programming algorithm for the allocation of selhng time to control units is presented, and a proof of the optimality of this solution under specified conditions is provided. This algorithm also generates the optimum sales force size and provides output which is a basis for designing sales territories. The allocation algorithm can accommodate a large class of multivariate response functions. The model also incorporates subjective judgment into the decision process. Interaction with sales management of a test firm has shown that the model is highly useful in pinpointing problem areas, in evaluating salesmen, and in designing territories which can, to a large degree, achieve the benefits of the optimum allocation generated by the model.